The dynamic effect of cash and non-cash payment instruments on money velocity in Indonesia - Dian Zulfa; Syahnur, Sofyan (Economic Journal of Emerging Markets, 2025)
Purpose — This study explores the dynamic effect of electronic money as a non-cash payment instrument on the velocity of money in Indonesia from 2012 to 2020.Method — Using quarterly time series data from 2012 to 2020, the research employs the Error Correction Model (ECM), stationarity, cointegration, and classical assumption tests to ensure the correct estimation procedure. Findings — The findings reveal several essential points: (1) Faster circulation of cash generally increases the velocity of M1; (2) Excessive money supply slows down M1 circulation; (3) An increase in the use of debit cards (ATMs) tends to reduce M1 velocity, while quicker credit card transactions can accelerate it; (4) Rapid circulation of electronic money can expedite M1, but large amounts can hinder it. Overall, both cash and non-cash money equally influence the behavior of M1 velocity in Indonesia. Implication — The government should focus more on money velocity to maintain stability, even though various payment instruments are utilized in the economy. Originality — The current research focuses on the dynamic development of modern finance in Indonesia and electronic money as non-cash payment instruments that impact money velocity.